Regular and epoch-making innovations in national urban planning - Kolyasnikov Victor A. (Архитектон)
The development of innovative urban planning in Russia and the USSR in the 18th – 20th century is considered. Innovative urban planning is defined as an activity to create innovations and introduce them into practice to obtain a specific effect. In the history of urban planning, this type of activity presents a cyclic-wave process with phases of rise and fall. The article proposes to adapt the concept of regular and epoch-making innovations developed in the field of economics to the conditions of innovative urban development. From this perspective, the author explores six innovative waves that are identifiable in the history of national urban planning in the above period.